Development of Scientific Approach-Based Learning Videos to Improve Student Learning Outcomes on Cell Biology - Hazeina Nasution, Adiba Nazila; Adlini, Miza Nina (FKIP Universitas Lampung, 2022)
The use of learning video media can attract students' attention so that it fosters curiosity and is motivated to learn. This study aims to determine the level of feasibility of learning video media based on the scientific approach that was developed. The eligibility criteria for the learning video used is validity. The development model used refers to the Borg and Gall model, where there are two main criteria, namely the design of learning videos and validation of learning videos. Assessment of the validity of the instructional video was evaluated by material experts and media experts. The test results are declared valid with an average percentage of 90% material experts, the average percentage of media experts is 90.8%. And the average percentage of the results of the limited field trial is 91.55%. The student learning outcomes have an N-Gain score of 0.60, this indicates a moderate category, the percentage of N-Gain Score is 60.09% with a fairly effective category. The overall results indicate that the learning video media based on a scientific approach is very feasible to be used as a medium for learning biology on cell material. The results of this study are expected to improve students' scientific thinking skills so that students have the ability to solve any problems they face and have high learning outcomes.Keywords: learning videos, scientific approach, research and development.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp844-853